2012
DOI: 10.1182/blood-2012-06-436055
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy is associated with similar survival compared with intensive chemotherapy in older patients with newly diagnosed acute myeloid leukemia

Abstract: We reviewed the outcome of 671 patients 65 years of age or older with newly diagnosed acute myeloid leukemia (AML) treated at our institution between 2000 and 2010 with intensive chemotherapy (n ‫؍‬ 557) or azacitidine-or decitabinebased therapy (n ‫؍‬ 114). Both groups were balanced according to cytogenetics and performance status. The complete response rates with chemotherapy and epigenetic therapy were 42% and 28%, respectively (P ‫؍‬ .001), and the 8-week mortality 18% and 11%, respectively (P ‫؍‬ .075). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
147
1
7

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(173 citation statements)
references
References 26 publications
18
147
1
7
Order By: Relevance
“…Although patients receiving either Aza or Dec induction were included in both studies, patients at MDACC received a 5-day Dec regimen in contrast to our patients, the majority of whom (63 of 83) received a 10-day decitabine (Dec10) induction. Despite these differences, Quintas-Cardama et al [44] reported similar results as ours with higher response rates following IC but no statistically significant differences in OS following either IC or Epi induction in older patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although patients receiving either Aza or Dec induction were included in both studies, patients at MDACC received a 5-day Dec regimen in contrast to our patients, the majority of whom (63 of 83) received a 10-day decitabine (Dec10) induction. Despite these differences, Quintas-Cardama et al [44] reported similar results as ours with higher response rates following IC but no statistically significant differences in OS following either IC or Epi induction in older patients.…”
Section: Discussionsupporting
confidence: 80%
“…In the univariate analysis, IC was associated with higher ORR (50% vs. 28%, P 5 0.001), CRR (43% vs. 20%, P 5 0.004), and median OS (10.7 vs. 9.1 months, P 5 0.012) as compared with Epi therapy [7,21,43,44]. However, when we performed a Cox proportional hazards regression model controlling for the baseline differences in patient characteristics and accounting for HSCT as a timedependent factor, we found no statistically significant difference in OS outcome based on induction choice (IC vs. Epi).…”
Section: Discussionmentioning
confidence: 96%
“…While the median OS in our study appears short in comparison with that reported by Fenaux et al from the comparison of azacitidine and BSC only (median, 19.1 vs 13.4 months), the studies are not directly comparable due to differences in the patient cohorts, as displayed by the OS of patients in the BSC arms [6]. The few retrospective studies that compared decitabine and azacitidine did not specifically assess the survival among patients with RAEBt and/or 20-30 % blasts [18][19][20][21][22]. Importantly, we also observed that the favorable impact of decitabine on the outcome of RAEBt patients was similar among various patient subgroups and significantly differed from that among RAEB patients.…”
Section: Survival In Subgroups Of Raebt Patientscontrasting
confidence: 65%
“…For example Quintas-Cardama et al found similar OS among 557 patients aged 65 given regimens generally containing ara-C at 1-2 g/m 2 daily 1 idarubicin or fludarabine 6 other agents and 114 patients given decitabine (n 5 67) or azacitidine (n 5 47) despite higher CR rates with the more intense therapies [40] (Fig. 7), thus again, as in the AML16 clofarabine trial [37] questioning the role of CR.…”
Section: Azacitidine and Decitabinementioning
confidence: 99%